2020
DOI: 10.9734/jammr/2020/v32i1930673
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease (COVID-19) Pandemic: Analysis of the Knowledge, Attitude and Practice among Healthcare Facilities in Jos, Nigeria

Abstract: Background: COVID-19 which was first reported in Wuhan China is now a global pandemic. Healthcare workers play a significant role in fighting this pandemic. The aim of this study is to assess the knowledge, attitude and practice (KAP) of COVID-19 among healthcare professionals in Jos. Methodology: The study population are all the health workers in Bingham University Teaching Hospital (BHUTH), Plateau State Specialist Hospital (PSSH) and ECWA comprehensive health care center (ECHC) in Jos who consented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The respondents consisted of correctional officers, healthcare workers, and chronic disease patients, residents of a conflict-affected area, urban slum dwellers, and sample populations from Nigeria, Egypt, Cameroon, Kenya, Uganda, Sudan, Sierra Leone, Libya, and Ethiopia. A study [14] In a study of 3712 Egyptians, most (70.2%) had high satisfactory knowledge of COVID-19 [18]. High educational level was associated with good knowledge.…”
Section: Studies On Knowledge and Adherence To Covid-19 Preventive Measuresmentioning
confidence: 97%
See 1 more Smart Citation
“…The respondents consisted of correctional officers, healthcare workers, and chronic disease patients, residents of a conflict-affected area, urban slum dwellers, and sample populations from Nigeria, Egypt, Cameroon, Kenya, Uganda, Sudan, Sierra Leone, Libya, and Ethiopia. A study [14] In a study of 3712 Egyptians, most (70.2%) had high satisfactory knowledge of COVID-19 [18]. High educational level was associated with good knowledge.…”
Section: Studies On Knowledge and Adherence To Covid-19 Preventive Measuresmentioning
confidence: 97%
“…An increased adherence to the health regulations laid down by the WHO would drastically reduce the COVID-19 burden. healthcare workers in Jos, Nigeria [14] showed that clinical healthcare workers had higher satisfactory practice scores (9.01 out of 12) compared to nonclinical healthcare workers (with an average score of 6.59). This gap could be attributed to their need for more precaution due to their relative closeness to patients and knowledge discrepancies when compared to nonclinical healthcare workers.…”
Section: Adherence To Covid-19 Preventive Measuresmentioning
confidence: 98%